2015
DOI: 10.1055/s-0040-1703882
|View full text |Cite
|
Sign up to set email alerts
|

An Educational Intervention Programme on Hazards of Plastic Waste and Its Disposal Among Adults: A Rural Community Based Study

Abstract: Introduction: Plastic is everywhere in today's lifestyle. It is used for packaging, protecting, serving, and even disposing of all kinds of consumer goods. Improper plastic disposal has become a leading problem in both developed and developing countries. As plastic is non-biodegradable in nature, it remains in environment for several years and disposing plastic wastes at landfill are unsafe and has led to various health problems. So researcher felt it is vital that adults should possess knowledge on hazards of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, the prudent approach is to choose healthy, high-quality plastic and use it properly. [12][13][14] It is inevitable to avoid plastic use. Although they are helpful for individuals, the challenges and costs associated with plastic disposal represent a burden on society.…”
Section: Introductionmentioning
confidence: 99%
“…However, the prudent approach is to choose healthy, high-quality plastic and use it properly. [12][13][14] It is inevitable to avoid plastic use. Although they are helpful for individuals, the challenges and costs associated with plastic disposal represent a burden on society.…”
Section: Introductionmentioning
confidence: 99%
“…A similar study conducted by (Manuel, J., et al, 2015) revealed that the pretest knowledge score was 42.52% and posttest knowledge score was 80.48% after administering effective teaching programme. The findings of this study shows that burning of plastic cause allergic asthma.…”
Section: Discussionmentioning
confidence: 69%
“…Participants with a higher level of education use plastic more frequently. Participants who receive higher levels of education use plastic less frequently, according to the research [ 19 , 20 ]. The study by Joseph et al among adults in Mangalore in 2016 found that greater awareness of plastic hazards was observed among participants with higher education levels [ 3 ].…”
Section: Discussionmentioning
confidence: 99%